2020
DOI: 10.31234/osf.io/3a85z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public Acceptance of Covid-19 Lockdown Scenarios

Abstract: Most countries have implemented nationwide lockdown policies aimed to decelerate the spread of SARS-CoV-2. Epidemiologists have recently discussed scenarios according to which these policies would need to be extended and/or intensified. To illuminate how the general public might react to such scenarios, we assessed Germans’ endorsement of and compliance with five specific scenarios. Results show that, in general, length of lockdown plays a more important role than intensity. Although half of the respondents re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Synchronized NPIs meant all countries implemented lockdowns at the same time, while unsynchronized NPIs meant half of all countries (randomly chosen for each simulation run) were under lockdown at any time. Cycling NPIs reflects the intermittent lockdowns that could occur if countries reinstate interventions after surpassing threshold numbers of new cases (25,26) various simulations where lockdown and non-lockdown periods were 3 or 4 weeks long over 2, 3, or 4 cycles in total. Across 1200 simulations, we found that synchronized cycles of NPIs were always more likely to end community transmission over 6 months, and generally lowered transmission further than if NPIs were unsynchronized (Fig.…”
Section: Modeling the Effect Of Synchronized Intermittent Npismentioning
confidence: 99%
“…Synchronized NPIs meant all countries implemented lockdowns at the same time, while unsynchronized NPIs meant half of all countries (randomly chosen for each simulation run) were under lockdown at any time. Cycling NPIs reflects the intermittent lockdowns that could occur if countries reinstate interventions after surpassing threshold numbers of new cases (25,26) various simulations where lockdown and non-lockdown periods were 3 or 4 weeks long over 2, 3, or 4 cycles in total. Across 1200 simulations, we found that synchronized cycles of NPIs were always more likely to end community transmission over 6 months, and generally lowered transmission further than if NPIs were unsynchronized (Fig.…”
Section: Modeling the Effect Of Synchronized Intermittent Npismentioning
confidence: 99%
“…Synchronized NPIs meant all countries implemented lockdowns at the same time, while unsynchronized NPIs meant half of all countries (randomly chosen for each simulation run) were under lockdown at any time. Cycling NPIs reflects the intermittent lockdowns that could occur if countries reinstate interventions after surpassing threshold numbers of new cases ( 25, 26 ). Therefore, this test helps predict what may happen if countries do not coordinate the easing and reinstating of NPIs based on regional rates of new cases.…”
Section: Figmentioning
confidence: 99%
“…Public acceptance for flexible and adaptive preventive restrictions is also considerably high in Germany, just like citizens' readiness to co‐implement restrictive measures (Gollwitzer et al . 2020). Furthermore, ad hoc research with regard to the policy preferences of German citizens revealed that a “large‐scale pandemic can induce a substantial willingness to give up freedom for casualty prevention” (Tepe et al .…”
Section: Collective Crash Course: Prevention Policies During the Covid‐19 Pandemicmentioning
confidence: 99%